Shrimp (Penaeus spp) Potential, Utilization (Penaeus spp) and Management Effort at Batang District Coastal Waters - Sulistyowati Sulistyowati; Muhammad Zainuri; Aziz Nur Bambang; Agung Suryanto (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
The study of potential and shrimp resource utilization (Penaeus spp.) at  Batang Regency coastal waters made based on analysis of the catching data and shrimp fishing trip during the period 2002-2011. Analysis of the catch per unit effort (CPUE) is used to predict the long-lasting potential (MSY) shrimp and optimum fishing effort. The analysis was also conducted to determine the state of fishing season based on quarterly data. MSY value and shrimp fishing effort in Batang respectively 29,032 kg and 18,262 trip. The highest shrimp fishing season was in the first quarter that is in January-March and decreased in the third quarter (July–September). It is known that the status of the shrimp fishery in 2005-2006 and in 2010-2011 have shown overfishing, so the effort settings required. The sustainable resources is more aimed at limiting the catch and the catch effort with arad net, ie 80% of the sustainable resources. Key words: Analysis of CPUE, shrimp (Penaeus spp.), MSY, Batang regency coastal waters.